(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article devoted to metaphors which used in terms of economy. And it indicates the interplay between language and economic thought, examining how metaphors shape our perceptions and interpretations of economic phenomena. Aim of this study is unveiling their cognitive, socio-political and rhetorical implications. And it discusses how necessary metaphors are in our life.